Using socioeconomics to counter health disparities arising from the covid-19 pandemic. (8th June 2020) - Anderson, Geoffrey; Frank, John William; Naylor, C David; Wodchis, Walter; Feng, Patrick
Abstract : Principles and methods drawn from decades of work showing that lower socioeconomic status is associated with poorer health should guide efforts to monitor and mitigate the impact of the covid-19 pandemic argue Geoffrey Anderson and colleagues